2022
DOI: 10.1093/jnen/nlac028
|View full text |Cite
|
Sign up to set email alerts
|

Azetidine-2-Carboxylic Acid-Induced Oligodendrogliopathy: Relevance to the Pathogenesis of Multiple Sclerosis

Abstract: The naturally occurring imino acid azetidine-2-carboxylic acid (Aze) is consumed by humans and can be misincorporated in place of proline in myelin basic protein (MBP) in vitro. To determine Aze effects on the mammalian CNS in vivo, adult CD1 mice were given Aze orally or intraperitoneally. Clinical signs reminiscent of MBP-mutant mice occurred with 600 mg/kg Aze exposure. Aze induced oligodendrocyte (OL) nucleomegaly and nucleoplasm clearing, dilated endoplasmic reticulum, cytoplasmic vacuolation, abnormal mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…Misincorporation of AZE is thought to alter the structural conformation of newly assembled proteins, resulting in protein misfolding and, consequently, ER-stress [ 38 ]. Sobel and collaborators have recently shown that administration of AZE to laboratory animals (especially young mice) triggers oligodendrocytes swelling, formation of microglial nodules and cell polarization [ 7 ], and providing essential proof-of-concept data to indicate that AZE consumption is associated with some degree of CNS pathogenicity. It is unclear though if AZE-induced protein misfolding is restricted to oligodendrocytes or it extends more globally to different CNS cell types, including microglia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Misincorporation of AZE is thought to alter the structural conformation of newly assembled proteins, resulting in protein misfolding and, consequently, ER-stress [ 38 ]. Sobel and collaborators have recently shown that administration of AZE to laboratory animals (especially young mice) triggers oligodendrocytes swelling, formation of microglial nodules and cell polarization [ 7 ], and providing essential proof-of-concept data to indicate that AZE consumption is associated with some degree of CNS pathogenicity. It is unclear though if AZE-induced protein misfolding is restricted to oligodendrocytes or it extends more globally to different CNS cell types, including microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its ability to evade recognition by transfer RNAs, the impostor AZE evades the editing process and is erroneously misplaced in lieu of the authentic L-proline, causing structural changes to L-proline-containing proteins [ 6 ]. According to Rubenstein’s initial theory [ 6 ], more recently supported by an interesting work from his colleagues [ 7 ], AZE misplacement increases the immunogenicity of certain myelin proteins, to likely initiate the autoimmune events leading to oligodendrogliopathy [ 8 ] and microgliosis [ 9 ], two known pathogenic features of MS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is conceivable that AZE misincorporation may contribute to the pathogenesis of both myelin and perhaps non-myelin associated CNS diseases. Sobel’s recent study supports this claim, as the authors demonstrated the dose-dependent detrimental effects of AZE administration on rodents’ myelin health, since the toxic NPAA caused severe oligodendrogliopathy and microglial clustering in the CNS white matter [ 8 ]. In line with these findings, our laboratory has recently explored the effects AZE exposure in the murine BV2 microglial cell line, where we revealed novel and potent pro-apoptotic and pro-inflammatory effects of the NPAA [ 7 ].…”
Section: Introductionmentioning
confidence: 89%
“…Upon its identification, Rubenstein developed a novel unifying hypothesis linking AZE consumption to multiple sclerosis (MS) pathogenesis, in which geographical and historical aspects of the disease were also taken into account [6]. Later studies revealed that the identified NPAA triggers specific pathological alterations in at least two resident cell populations of the central nervous system (CNS), oligodendrocytes and microglia [7,8], corroborating the initial pathogenic link with MS. AZE exhibits high structural similarity with L-proline [9]. For this reason, upon its entry into cells, AZE can evade recognition by aminoacyl-tRNA synthetases (aaRS) and be misincorporated into the sequence of proline-rich proteins upon consumption [6,10].…”
Section: Introductionmentioning
confidence: 98%